An in vivo detection system for transient and low‐abundant protein interactions and their kinetics in budding yeast - Brezovich, Andrea (Yeast, 2015)
Methylation tracking (M‐Track) is a protein‐proximity assay in Saccharomyces cerevisiae, allowing the detection of transient protein–protein interactions in living cells. The bait protein is fused to a histone lysine methyl transferase and the prey protein to a methylation acceptor peptide derived from histone 3. Upon interaction, the histone 3 fragment is stably methylated on lysine 9 and can be detected by methylation‐specific antibodies. Since methylation marking is irreversible in budding yeast and only takes place in living cells, the occurrence of artifacts during cell lysate preparation is greatly reduced, leading to a more accurate representation of native interactions. So far, this method has been limited to highly abundant or overexpressed proteins. However, many proteins of interest are low‐abundant, and overexpression of proteins may interfere with their function, leading to an artificial situation. Here we report the generation of a toolbox including a novel cleavage‐enrichment system for the analysis of very low‐abundant proteins at their native expression levels. In addition, we developed a system for the parallel analysis of two prey proteins in a single cell, as well as an inducible methylation system. The inducible system allows precise control over the time during which the interaction is detected and can be used to determine interaction kinetics. Furthermore, we generated a set of constructs facilitating the cloning‐free genomic tagging of proteins at their endogenous locus by homologous recombination, and their expression from centromeric plasmids. GenBank submissions: pCK900; KM407502, pCK901; KM407503, pCK902; KM407504, pCK903; KM407505, pCK904; KM407506, pCK905; KM407507, pCK906; KM407508, pCK907; KM407509, pCK908; KM407510, pCK909; KM407511, pCK910; KM407512, pCK911; KM407513. © 2015 The Authors. Yeast published by John Wiley & Sons Ltd.